Data Sparseness and Variance in Accounting Profitability - Spyridon Stavropoulos; Martijn J. Burger; Dimitris Skuras (Tinbergen Institute, 2015)
A central question in strategic management is why some firms perform better than others. One approach to addressing this question empirically is to decompose the variance in firm-level profitability into firm, industry, location, and year components. Although it is well established that data sparseness in variance decomposition studies can lead to overestimating particular variance components, little attention has been paid to sample size requirements in strategic management studies that have examined the nature of differences in firm profitability. We conduct a meta-regression and variance decomposition study and conclude that the variation in the results from previous studies is drivento a considerable extentby the number of observations per group within a component. Based on these findings, we draw conclusions regarding the validity and reliability of previo us variance decomposition studies and provide implications for current debates in the strategic management literature.
Keywords: C18; L16; R11; 330; Firm profitability; variance decomposition; data sparseness; meta-analysis